Mechanism of Action of Lacticaseibacillus paracasei HNU502 and Fecal Microbiota Transplantation in Alleviating Antibiotic Side Effects - CHEN Lin, LI Ao, LI Jiahe, ZHANG Zeng, ZHANG Jiachao (Shipin Kexue)
Antibiotics are effective in treating bacterial infections, but they also disrupt the gut microbiota, thereby causing side effects such as diarrhea, flatulence and indigestion. Probiotics and fecal microbiota transplantation (FMT) have attracted widespread attention due to their ability to restore the balance of the gut microbiota and alleviate various conditions. In this study, the mechanism of action of FMT and the probiotic Lacticaseibacillus paracasei HNU502 in alleviating the side effects of cefotaxime, a common antibiotic, using combination of metagenomics, pathological analysis and gas chromatography. The findings suggested that FMT alleviated antibiotic side effects by restoring the disturbed gut microbiota, while HNU502 worked by reestablishing the balance of the gut microbiota. Both FMT and probiotic supplementation improved gut microbiota composition, but to varying degrees, prevented goblet cell loss, and increased the contents of mucin-2 (MUC-2) and zonula occludens-1 (ZO-1), thus aiding gut mucosal recovery. Moreover, the two approaches ameliorated the metabolic disorders of short-chain fatty acids, inhibited the secretion of pro-inflammatory cytokines such as interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α as well as blood urea nitrogen (BUN), and effectively reduced virulence factor enrichment. This study contributes to a better understanding of the link between human health and gut microbiota, and provides new therapeutic options for mitigating antibiotic side effects, which is of great significance for improving patients’ health status and quality of life.